2018
DOI: 10.1177/2167479517753117
|View full text |Cite
|
Sign up to set email alerts
|

Relaying Rio Through an Australian Gaze: Australian Nationalistic Broadcast Focus in the 2016 Summer Olympic Games

Abstract: This study explored how potential national biases unfolded within the Australian broadcast of the 2016 Rio Summer Olympics. Applying social identity theory and self-categorization theory, this study content analyzed a total of 45 prime time broadcast hours of Australia’s Seven Network’s coverage of the Rio Games. Although the majority of top 20 most-mentioned athletes were Australian, non-Australian athletes were mentioned more frequently regarding total name mentions. Moreover, Australian athletes and non-Aus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(24 citation statements)
references
References 60 publications
(102 reference statements)
3
20
1
Order By: Relevance
“…Situation with women's sport coverage changes during Olympic Games when media pay more attention to compatriot women athletes and gender is outweighed by national pride for sport achievements (Vincent et al 2018;Billings et al 2019;Scott et al 2019). Billings et al (2014) examined coverage of Olympics by NBC and revealed that during 2012 Games «the first time women received more overall clock-time than men, the first time women tallied more appearances than men in the most-mentioned athletes category, and the first time women athletes received more overall mentions than male athletes.» The researchers explain the salience of women athletes in the air by the fact that women's team surpassed the achievements of men's team and won more medals.…”
Section: Towards Gender Equality: Media Coverage In Olympic Games Periodmentioning
confidence: 99%
“…Situation with women's sport coverage changes during Olympic Games when media pay more attention to compatriot women athletes and gender is outweighed by national pride for sport achievements (Vincent et al 2018;Billings et al 2019;Scott et al 2019). Billings et al (2014) examined coverage of Olympics by NBC and revealed that during 2012 Games «the first time women received more overall clock-time than men, the first time women tallied more appearances than men in the most-mentioned athletes category, and the first time women athletes received more overall mentions than male athletes.» The researchers explain the salience of women athletes in the air by the fact that women's team surpassed the achievements of men's team and won more medals.…”
Section: Towards Gender Equality: Media Coverage In Olympic Games Periodmentioning
confidence: 99%
“…K. M. Scott et al, 2012; Vincent & Crossman, 2012). Nationalized coverage of sporting events occurs worldwide, from America (Angelini et al, 2012; Billings et al, 2008) to Canada (Angelini et al, 2017; MacArthur et al, 2017), Australia (Eagleman et al, 2014; O. Scott et al, 2019; O.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As a result, researchers have used the number of name mentions of home nation and foreign athletes to examine the salience of nationality during Olympic broadcasts. For example, Scott et al (2019) found that since the majority of named athletes during Australian coverage of the 2016 Rio Olympic Games were Australian, viewers’ opinions of Australia’s success may have been skewed due to the frequency of Australians named in coverage. Similarly, Angelini and colleagues (2017) found that from a Canadian broadcaster, all of the top 20 most-mentioned athletes of the 2014 Winter Olympics were Canadian.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations